Management of damping off disease in tomato (Solanum lycopersicum) using potential biocontrol agent Pseudomonas fluorescens - SUMA, MOKA; SINGH, NARINDER; BUTTAR, DALJEET SINGH; HUNJAN, MANDEEP SINGH (The Indian Journal of Agricultural Sciences, 2023)
Biocontrol is a potential strategy adapted to control the fungal plant pathogens thus bio-prospecting to find novel native siderophore and enzyme producing Pseudomonas isolate for the management of tomato (Solanum lycopersicum L.) damping off disease under the prevailing conditions of Punjab state. In the present study, a total of 15 isolates of Pseudomonas fluorescens isolated from rhizospheric soils of tomato growing areas of Punjab and evaluated by dual culture plate confrontation assay, of which, two isolates (Pf10 and Pf6) showed maximum antagonistic activity against damping off pathogen (Rhizoctonia solani) with a zone of inhibition 14.30 mm and 11.53 mm respectively. These Pseudomonas isolates (Pf10 and Pf6) were also analyzed for their siderophore production and enzymatic activity. They were found to effectively produce siderophore and cell wall degrading enzymes such as chitinase and β-1,3 glucanase with higher antagonistic activity against Rhizoctonia solani. The present study was carried out at the Plant Pathology Research Farm, Punjab Agricultural University, Ludhiana, Punjab during 2017 and 2018 to confirm the bio-efficacy of these Pseudomonas isolates. Amongst the isolates, talc-based bioformulation of Pf10 isolate when applied as the seed+soil treatment had exerted strong inhibition against Rhizoctonia solani in tomato. Therefore, based on the findings, it was concluded that Pseudomonas fluorescens played a significant role as a potential biocontrol agent against damping off disease in tomato.